An Enactive-Ecological Approach to Information and Uncertainty - Carvalho, Eros Moreira de; Rolla, Giovanni (Frontiers in Psychology, 2020)
In this paper, we approximate ecological psychology to enactivism through the idea of minimization of uncertainty. Our main thesis is that both the idea of information at play in ecological psychology, what we call information for action; and the idea of information as covariance put forth by some enactivists can be construed as a matter of minimization of uncertainty through skilled performance, which does not, by itself, implies representational content. We argue that the agent’s cognitive system conveys information for acting in an environment by minimizing uncertainty about how to achieve her intended goals in that environment, and we address the challenge of explaining how skilled agency can be adapted to deal with unforeseen circumstances and successfully minimize uncertainty in new cases. We conclude by reviewing empirical findings that support our view and by showing how direct learning, seen as instance of ecological rationality at work, is the core engine by which mere possibilities for action are turned into embodied know-how. Finally, we indicate the affinity between direct learning and sense-making activity.